Testing the Appropriateness of Lumped Hydrological Model in Groundwater Recharge Estimation for a Small Catchment in Karnataka, India (International Journal of Environmental Sciences, 2025)
Groundwater recharge, being a major factor monitoring groundwater resources, should be carefully analyzed in order to establish the quantities of water that are available for pumping without dangerously depleting groundwater reserves, but also to determine the groundwater vulnerability. And hence, Quantification of groundwater recharge is a major problem in many water resource investigations. It is a complex function of meteorological conditions, physiographic characteristics and properties of the geological material within the paths of flow. To estimate the groundwater recharge a physically-based lumped hydrological model is developed for modeling groundwater levels in response to precipitation timeseries and groundwater abstractions by pumping. The model performance is assessed by comparing predicted and observed groundwater levels. In any modeling exercise their being a need for parameter optimization, Generalized likelihood Uncertainty Estimation methodology (GLUE) is widely-used for quantifying uncertainty in groundwater recharge mapping. In order to improve the reliability and performance of the lumped- hydrological model, in this study a general approach for the assessment of performance in the simulation of groundwater recharge estimation is proposed. Sensitivity analysis results indicate that the groundwater recharge is more sensitive to parameters related to climatic conditions, soil characteristics and land use.